Effect of ambient pressure on ammonia sprays using a single hole injector - Shen, L; Leach, F (SAE International, 2024)
Ammonia has received attention as an alternative hydrogen carrier and a potential fuel for thermal propulsion systems with a lower carbon footprint. One strategy for high power density in ammonia applications will be direct injection of liquid ammonia. Understanding the evaporation and mixing processes associated with this is important for model development. Additionally, as a prior step for developing new injectors, it is of interest to understand how a conventional gasoline direct injection (GDI) injector would behave when used for liquid ammonia without any modifications. Pure anhydrous ammonia, in its liquid form, was injected from a single hole GDI injector at a fuel pressure of 150 bar into an optically accessible constant volume chamber filled with nitrogen for ammonia spray measurements. The chamber conditions spanned a wide range of pressures from 3 - 15 bar at an increment of 1 or 2 bar between the test points. These conditions lead to sprays which are both flash boiling and non-flash boiling as well as a transition region. Spray morphology studies were performed based on high-speed backlit images recorded at 10 kHz. Droplet size distributions for the bulk spray were simultaneously measured using a laser diffraction technique at the same sampling rate. The results show that at a higher ambient pressure, shorter spray penetration lengths and smaller spray spread widths are observed compared to those at lower pressures. While these macroscopic spray geometrical parameters change gradually at different ambient pressures, the droplet size distribution undergoes a slightly more abrupt transition across the saturation vapor pressure at chamber temperature. These results provide a fundamental dataset for liquid ammonia injection and could be used to validate against simulation data or to build surrogate models.